2011
DOI: 10.3155/1047-3289.61.4.418
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Mercury Reaction Chemistry on Activated Carbon

Abstract: Experimental and theory-based investigations have been carried out on the oxidation and adsorption mechanism of mercury (Hg) on brominated activated carbon (AC). Air containing parts per billion concentrations of Hg was passed over a packed-bed reactor with varying sorbent materials at 140 and 30°C. Through X-ray photoelectron spectroscopy surface characterization studies it was found that Hg adsorption is primarily associated with bromine (Br) on the surface, but that it may be possible for surfacebound oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…The binding energy of *101 eV for 4f 7/2 in the spectra of Hg-saturated AC (Fig. 3a) confirmed the presence of Hg-O and Hg-Cl bonds (Nelson et al 2000;Wilcox et al 2011). In the case of mercury-saturated AC-DMDS (Fig.…”
Section: Mercury Adsorption By Sulfurized Activated Carbonssupporting
confidence: 52%
“…The binding energy of *101 eV for 4f 7/2 in the spectra of Hg-saturated AC (Fig. 3a) confirmed the presence of Hg-O and Hg-Cl bonds (Nelson et al 2000;Wilcox et al 2011). In the case of mercury-saturated AC-DMDS (Fig.…”
Section: Mercury Adsorption By Sulfurized Activated Carbonssupporting
confidence: 52%
“…Also, the Si2p spectral lines of Si-C, silicon dioxide (SiO 2 ) and Si compounds are expected to be in the region between 98.5 eV and 104 eV. The Si2p core-level spectra can be separated from Hg4f spectra by using the area of the Si2s core-level spectra and the intensity ratios of the two Si spectral lines [10]. Table 2 provides a summary of the XPS of Hg and Br binding energies for Hg-Br reference compounds [29,30] and for the Hg-containing brominated AC sorbent investigated in the current work compared against the study carried out by Hutson et al [6].…”
Section: Resultsmentioning
confidence: 99%
“…with brominated AC likely involves Hg interaction with the surface-bound Br by possibly detaching/replacing it from the graphene edge site. The effect of O on the binding of Hg in the presence of Br atom has been investigated in our previous work [10]. It was found that the edge C binds to Hg more tightly when it is located next to a surface O atom, but not immediately next to a bound Br atom [10].…”
Section: Chemical Nature Of Bound Mercury Species From Dftmentioning
confidence: 98%
See 2 more Smart Citations